Influence of High-Fidelity Manikin-Based Simulation on Nursing Students' Basic Cardiac Life Support Ability and Motivation - Ni Luh Putu Inca Buntari Agustini; I Putu Budiarsana; I Kadek Artawan; Only Hufana; Dewi, Ni Putu Ayu Ratna (Babali Nursing Research, 2024)
Introduction: One of the competencies that nursing students must have while dealing with cardiac arrest is the capacity to perform critical life support, namely basic cardiac life support (BCLS). Having the abilities and motivation to perform BCLS is a complex process and often goes beyond the planned laboratory session's timeframe. The study wanted to determine the intervention’s impact on nursing students' ability and motivation to conduct BCLS. Methods: This study employed a quasi-experimental design with a pre-post-test control group and was carried out in July 2023 at the Emergency Skills Lab with fourth-year undergraduate nursing students. In this study, the sample size for the control and intervention groups was 52 for each group, selected using a simple random sampling technique. The independent variable was high-fidelity manikin-based human patient simulation based on Kolb's experiential learning theory, while the dependent variables were BCLS abilities measured using a mega code checklist and student motivation measured using a valid and reliable motivation questionnaire. Data were examined using the independent sample t-test. Results: The independent t-test results for the motivation variable showed a significant difference (p = 0.004), indicating a significant difference in motivation among students before and after being exposed to high-fidelity manikin-based human patient simulation based on Kolb's experiential learning theory in performing BCLS. Conclusion: High-fidelity manikin-based Human Patient Simulation is an educational paradigm in healthcare that involves using manikins that closely resemble real patients in realistic scenarios. It can be used as an alternative teaching method to boost BCLS performance and motivation.